TINJAUAN HUKUM TERHADAP UNDANG¬-UNDANG NO 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK BERKAITAN DENGAN PENYITAAN HP DI SEKOLAH BERDASARKAN PERSPEKTIF FIQH SIYASAH - Nauli, Shinthia Asih; Fatimah, Fatimah (UNES Law Review, 2023)
Confiscation is one of the forced measures regulated in the Criminal Procedure Code (KUHAP). This often happens in every school holding students' cellphones confiscated without clear knowledge. In fact, the school not only confiscated students' cellphones but also checked the contents of the cellphone, this action was allegedly against the law. Even though the school cannot search the contents of students' cellphones without clear permission because everyone has the right to freedom, to privacy, and also to personal data. Based on Article 26 paragraph (1) in conjunction with Article 30 paragraph (1) Law No. 19 of 2016 concerning Information and Electronic Transactions. With the legal review, it is hoped that the school does not violate human rights, including confiscating cellphones at school, the school is not arbitrary in carrying out forced searches of students. This research is a empirical juridical law research with statutory and conceptual approaches. The results of this study are that law enforcement in carrying out forced searches of students' cellphones cannot be arbitrary, but the implementation of these searches must be based on or be based on an applicable statutory regulation.